Combined Intranasal Insulin/Saxagliptin/Metformin Therapies Ameliorate the Effect of Combined Oral Contraceptive- (COC-) Induced Metabolic Syndrome (MetS) with a Major Target on Glucose Metabolism in Adult Female Wistar Rats. (13th December 2021) - Afolabi, Saheed Olanrewaju; Folahan, Joy; Agede, Olalekan; Olorundare, Olufunke
Abstract : Objective . To evaluate the effect of the chronic use of combined oral contraceptives (COCs: ethinyl estradiol and levonorgestrel) on the indices of metabolic syndrome in adult female Wistar rats and possible therapeutic management. Materials and Methods . 64 female Wistar rats received either distilled water, norethindrone (NOR), COC, intranasal insulin (INI), metformin (MET), saxagliptin (SAX), INI+MET, and INI+SAX. After 8 weeks of exposure to COC, the animals were sorted into the therapeutic groups. Several parameters were assayed for, such as body weight changes, fasting blood glucose (FBG) level, insulin levels, inflammatory cytokines, and glycated hemoglobin (Hb1Ac). Results . The levels of FBG, insulin, and Hb1Ac were increased consequent upon COC treatment. Treatment with INI+SAX and INI+MET reduced significantly the levels of FBG and Hb1Ac; in addition, the level of insulin was significantly increased in the INI+MET groups (p ≤ 0.05 ). Serum lipid profile analysis showed a statistical reduction in high-density lipoprotein (HDL) level; this reduction was also significantly reversed in the INI+SAX group. Reduced catalase activity observed in the COC group was reversed in the INI+MET group (p ≤ 0.05 ). A nonsignificant increase in the level of TNF- α as a result of COC treatment was reversed by INI and INI+MET treatment. Liver GLUT4 and G-6-phosphate levels were significantly increased by COC treatment, and this effect was reversed by INI+SAX in both assays, respectively (p ≤ 0.01 ). Conclusions . The use of MET and SAX in combination with INI has been shown to reverse some indices of MetS. This study proposes a clinical phase to backup and ascertain these preclinical findings.